Effects of Family Caregivers’ Preparedness Program on Preventing Aspiration in Older Patients with Dysphagia - Hermsuwan, Sirirat; Wirojratana, Virapun; Wattanakitkrileart, Doungrut; Aroonlueng, Aukarachi (Journal of The Royal Thai Army Nurses, 2024)
This study aimed to examine the effects of family caregivers’ preparedness program on preventing aspiration in Thai older patients with dysphagia, a randomized control trial. The participants were family caregivers aged 20 years and above, male and female who take care of older patients are admitted in a private hospital in Bangkok. The participants were comprised of 42 family caregivers and randomly assigned to the two study group (n = 21 per group). There were 21 family caregivers in the control group who received routine nursing care and 21 family caregivers in the experimental groups who received routine nursing care and the preparedness program, 4-day program duration, 15-45 minutes each day. Data collection was performed by using demographic questionnaires, and the Preparation for Caregiving form. Descriptive statistics and t-test were used to analyze the data. The results showed that the family Caregivers’ Preparedness Program on Preventing Aspiration in Older Patients with Dysphagia in the experimental group were significantly higher than those in the control group with statistical significance (t = 5.79, p = .00). Since the patient has been admitted, nurses could encourage family to take part in caring to develop the competency and preparedness of caregivers from the hospital to home and to develop the role of nurses in caring for patients before discharge from the hospital to be more efficient.